Experiences of families of trans and gender diverse youth in Portugal within an ecological systems framework - Carmona, M. J.; Pinto, N.; Moleiro, C. (Portuguese Journal of Social Science, 2021)
Trans people’s civil rights and visibility on issues related to gender identity have come a long way in the last decade in Portugal and worldwide. This article presents a study focused on the experiences of families of trans and gender diverse youth. It aims to understand and examine the experiences, considerations and challenges that parents, siblings and other relatives of young trans and gender diverse people encounter within the current Portuguese context. Eleven participants from six family units were interviewed, with the degrees of kinship of mother (n = 4), father (n = 3), sister (n = 3) and grandmother (n = 1). Results show a diversity of positive and less positive experiences, resources and challenges within the nuclear and extended families, within the educational and health systems and, lastly, within the larger social and cultural context. Main implications and recommendations for intervention and public policies in this field are presented.